CONCEPTUAL DEFINITION: DISTINGUISHING ANTITHESIS FROM ANTONYMY AND SIMPLE CONTRAST (SCIENCE TIME JOURNAL, 2026)
This article can be annotated by highlighting examples of each concept, noting the parallel structures in antithesis, identifying word pairs exhibiting antonymy, and listing the points of difference in simple contrasts. The exploration of language and its nuances has long fascinated scholars across various disciplines, particularly in linguistics and rhetoric. Among the key concepts that have garnered attention are antithesis, antonymy, and simple contrast. These terms, while related to the idea of opposition, serve distinct functions in communication. Several notable scholars have contributed to our understanding of these concepts.